2021
DOI: 10.3390/ijerph18020521
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Land Comprehensive Carrying Capacity and Spatio-Temporal Analysis of the Harbin-Changchun Urban Agglomeration

Abstract: Land comprehensive carrying capacity (LCCC) reflects the limits of urban development that the land ground in the spatial area can bear under the constraints of society, economy, resources, and environment. An accurate and objective evaluation of LCCC is of great significance to the rational planning of urban space. Using the entropy method to obtain the weights of evaluation indexes, this study constructed an index system composed of four subsystems, i.e., urban construction (UC), social economy (SE), industry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…The third is to improve the effectiveness of land development. The focus should be on strengthening the supervision of land use in Jiayuguan, Jinchang, Baiyin, Tianshui, Pingliang, Huating, and other cities, regularly carrying out evaluations of the intensive use of urban construction land, accelerating the establishment of a mechanism linking land development performance to indicator allocation, and gradually reducing the dependence of urban development on land resource consumption and moving into strong decoupling [140,141].…”
Section: Incremental Development Policy Areamentioning
confidence: 99%
“…The third is to improve the effectiveness of land development. The focus should be on strengthening the supervision of land use in Jiayuguan, Jinchang, Baiyin, Tianshui, Pingliang, Huating, and other cities, regularly carrying out evaluations of the intensive use of urban construction land, accelerating the establishment of a mechanism linking land development performance to indicator allocation, and gradually reducing the dependence of urban development on land resource consumption and moving into strong decoupling [140,141].…”
Section: Incremental Development Policy Areamentioning
confidence: 99%
“…Spatial distribution analysis of carrying capacity is also used for planning the distribution of activities and selection of alternatives, as well as for transferring economic activities to the regions that possess the capacity to support them (Tang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the per capita ecological footprint in these six metropolitan areas in 2016 was 4.01, 4.02, 3.66, 3.25 and 3.94 gha/person, respectively, which are all higher than the international average value on the per capita ecological footprint of 1.7 gha/person in 2016. On the other hand, LRCC from the perspective of regional carrying status based on multi-factors follows the research path of "land→population", which integrates various factors affecting LRCC, as shown in studies [21][22][23]. However, the result from using a multi-factor research path is considered to not be helpful for a government's policy planning [11].…”
Section: Introductionmentioning
confidence: 99%